Pemanfaatan Teknologi Informasi dan Pengaruhnya Terhadap Kinerja Pelaku Usaha Kecil Menengah di Kota Padang - Arkilaus Samaloisa; Dian Yustiana; Detman Detman (Fakultas Sastra Universitas Ekasakti, 2023)
The development of rapid technology has affected all facets of life, as well as in the business wold, including small and medium enterprises. However, not all small and medium enterprises are able to maximize the use of information technology. For that we need to see how the actual use of information technogy and its impact n small and medium enterprises in the city of Padang. The object of research is chosen in this study is the small and medium enterpreneurs in the city of padang in accordance with the domicile researchers. Samples were 30 taken by using a convenience sampling technique with criteria small and medium enterprises enterpreneurs engaged in trade of food industri like restaurant business, snack businesses and others. Based on the results of the study, obtained the following regression equation : Y = 15.851 + 0.437 X. Based on the analysis of the use of inpormation technology variable effect on the performance of small and medium enterprises in the city of Padang. Because the analysis of data wiht a simple linear analysis of knomn significance value of 0,000 and significance value is less than the alpha of 0,05. Thus it can be concluded that the use of information technology has a positive effect n the performance of small and medium businesses.